1994
DOI: 10.1029/93wr03037
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of surface flux measurements in heterogeneous terrain during the Monsoon '90 experiment

Abstract: A network of 9-m-tall surface flux measurement stations were deployed at eight sparsely vegetated sites during the Monsoon '90 experiment to measure net radiation, Q, soil heat flux, G, sensible heat flux, H (using eddy correlation), and latent heat flux, ire (using the energy balance equation). At four of these sites, 2-m-tall eddy correlation systems were used to measure all four fluxes directly. Also a 2-m-tall Bowen ratio system was deployed at one site. Magnitudes of the energy balance closure (Q + G + H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
70
1
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 28 publications
6
70
1
2
Order By: Relevance
“…The largest residual to energy budget closure during the Monsoon'90 experiment (Kustas et al, 1991) occurred at the poorest-rated site (in terms of flatness and slope), with a value of 36 W m −2 (Stannard et al, 1994). Typical midday Bowen-ratio values were near 1.0.…”
Section: Review Of Surface Flux Measurements and Energy-balance Closurementioning
confidence: 99%
See 2 more Smart Citations
“…The largest residual to energy budget closure during the Monsoon'90 experiment (Kustas et al, 1991) occurred at the poorest-rated site (in terms of flatness and slope), with a value of 36 W m −2 (Stannard et al, 1994). Typical midday Bowen-ratio values were near 1.0.…”
Section: Review Of Surface Flux Measurements and Energy-balance Closurementioning
confidence: 99%
“…At a semi-arid Sonoran desert site, Unland et al (1996) measured fluxes to within an average closure of 96% over a year. Unfortunately, no data were available to show if, or how, closure rates changed after precipitation during either of these studies, but during the dry season in Arizona, flux measurements from Stannard et al (1994) showed little change in closure after a rainfall.…”
Section: Review Of Surface Flux Measurements and Energy-balance Closurementioning
confidence: 99%
See 1 more Smart Citation
“…Para isso, a curva experimental da retenção de água no solo necessita ser descrita matematicamente. O modelo proposto por van Genuchten (1980) para expressar analiticamente a curva de retenção tem-se mostrado bastante eficiente e seu uso já é bastante difundido (van Genuchten et al, 1991). A equação proposta por van Genuchten (1980) é: …”
Section: Parametrização Das Funções Hidráulicas Do Solounclassified
“…Idso et al (1975), on the other hand, found that for bare soil conditions, the slopes of the G versus R n relationships essentially doubled in going from wet to dry soil, which implies that for a given R n , the G value would be higher for a dry soil compared to a wet soil. The effects of spatial variability on G measurements can be significant and have been discussed by Fritton et al (1976) and by Stannard et al (1994).…”
mentioning
confidence: 99%